Radiosynthesis of an 18 F-fluoroglycosylated aminoferrocene for in-vivo imaging of reactive oxygen species activity by PET - Toms, Johannes; Reshetnikov, Viktor; Maschauer, Simone; Mokhir, Andriy; Prante, Olaf (Journal of Labelled Compounds & Radiopharmaceuticals, 2018)
The imaging of reactive oxygen species (ROS) at the molecular level with high sensitivity and specificity by positron emission tomography (PET) could be of enormous interest to increase our knowledge about ROS activity and signalling, especially in tumours. The aim of this research was to optimise the click chemistry-based radiosynthesis of an 18 F-labelled aminoferrocene glycoconjugate that was derived from an N-alkylaminoferrocene lead structure known to have anticancer activity in vitro. Applying the solvent system phosphate buffer/THF (12/5), Cu(OAc)2 and sodium ascorbate as reducing agent at 60°C, the alkyne 1 reacted with the 18 F-labelled glycosyl azide [18 F]2 in the presence of carrier 3 (47μM) to obtain carrier-added [18 F]4 in a radiochemical yield of 85%. Interestingly, the addition of carrier was essential for sufficient radiochemical yield, because it suppressed the oxidation of no-carrier-added (n.c.a.) [18 F]4. Future work will include the formulation of c.a. [18 F]4 for studying its biodistribution in tumour-bearing mice.
EVALuna2:212380